2006
DOI: 10.1080/15216540600791555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclosporin A, FK506 and rapamycin on calcineurin phosphatase activity in mouse brain

Abstract: SummaryCalcineurin is a Ca 2+ /calmodulin-dependent protein phosphatase expressed at high levels in brain. The immunosuppressive drugs cyclosporin A and FK506, but not rapamycin are specific inhibitors of calcineurin, the inhibitory effects of which have been elucidated in the immune system. Here by using these compounds as inhibitors, we assayed the enzyme in mouse brain after injection of 12.5 nmol cyclosporin A, FK506, or rapamycin into the left lateral ventricle of mouse brain. Data from calcineurin activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…To test the involvement of calcineurin in sFlt-1 production, pregnant mice were infused with Ang II with or without daily subcutaneous injection of FK506, a well-known selective calcineurin inhibitor. 29,30 As shown in Figure 4A, the increased sFlt-1 secretion induced by Ang II at gestation days 15 and 17 was completely inhibited by FK506, indicating that the induction of sFlt-1 by Ang II is mediated through calcineurin signaling in vivo. We also found that FK506 is able to attenuate the elevated systolic blood pressure and reduced fetal growth resulting from Ang II infusion (Table).…”
Section: At 1 Receptor Activation Induces Sflt-1 Release Via the Calcmentioning
confidence: 95%
“…To test the involvement of calcineurin in sFlt-1 production, pregnant mice were infused with Ang II with or without daily subcutaneous injection of FK506, a well-known selective calcineurin inhibitor. 29,30 As shown in Figure 4A, the increased sFlt-1 secretion induced by Ang II at gestation days 15 and 17 was completely inhibited by FK506, indicating that the induction of sFlt-1 by Ang II is mediated through calcineurin signaling in vivo. We also found that FK506 is able to attenuate the elevated systolic blood pressure and reduced fetal growth resulting from Ang II infusion (Table).…”
Section: At 1 Receptor Activation Induces Sflt-1 Release Via the Calcmentioning
confidence: 95%
“…To further confirm that these behavioral effects were specific to calcineurin inhibition, we performed a negative control experiment with rapamycin, which binds to FKBP but does not inhibit calcineurin activity (Liu et al, 1991;Yu et al, 2006). Once again, nicotine administration led to locomotor sensitization across testing days (F (3,27) ϭ 2.944; p ϭ 0.05) (Fig.…”
Section: Calcineurin Inhibition In the Vta Attenuates Nicotine-mediatmentioning
confidence: 99%
“…In addition, since cyclosporine is an immunophilin which must bind to cyclophilin in order to inhibit calcineurin (Liu et al 1991), it is possible our results could be due to the immunophilin effects of cyclosporine that are independent of calcineurin inhibition. To address this possibility, we performed an additional experiment with rapamycin, an immunophilin that does not inhibit calcineurin (Liu et al 1991;Yu et al 2006). While control animals showed enhanced locomotor activity upon acute cocaine injection (Rap 0 mg, p < 0.05, independent samples ttest, Fig 2D), pretreatment with rapamycin (15 mg/kg) did not affect cocaine-induced locomotor activity (p > 0.05, independent samples t-test, Fig 2D).…”
Section: Systemic Cyclosporine Pretreatment Leads To a Sensitized Locmentioning
confidence: 99%